TS-SEP: Joint Diarization and Separation Conditioned on Estimated Speaker Embeddings - Boeddeker, Christoph; Subramanian, Aswin Shanmugam; Wichern, Gordon; Haeb-Umbach, Reinhold; Le Roux, Jonathan (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Keywords: Electrical and Electronic Engineering; Acoustics and Ultrasonics; Computer Science (miscellaneous); Computational Mathematics

Geodesic Interpolation of Frame-Wise Speaker Embeddings for the Diarization of Meeting Scenarios - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2024 - 2024 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

On the Integration of Sampling Rate Synchronization and Acoustic Beamforming - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (European Signal Processing Conference (EUSIPCO))

Frame-Wise and Overlap-Robust Speaker Embeddings for Meeting Diarization - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

LibriWASN: A Data Set for Meeting Separation, Diarization, and Recognition with Asynchronous Recording Devices - Schmalenstroeer, Joerg; Gburrek, Tobias; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)

A Teacher-Student Approach for Extracting Informative Speaker Embeddings From Speech Mixtures - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (INTERSPEECH 2023)

On Feature Importance and Interpretability of Speaker Representations - Rautenberg, Frederik; Kuhlmann, Michael; Wiechmann, Jana; Seebauer, Fritz; Wagner, Petra; Haeb-Umbach, Reinhold (ITG Conference on Speech Communication)
Unsupervised speech disentanglement aims at separating fast varying from slowly varying components of a speech signal. In this contribution, we take a closer look at the embedding vector representing the slowly varying signal components, commonly named the speaker embedding vector. We ask, which properties of a speaker's voice are captured and investigate to which extent do individual embedding vector components sign responsible for them, using the concept of Shapley values. Our findings show that certain speaker-specific acoustic-phonetic properties can be fairly well predicted from the speaker embedding, while the investigated more abstract voice quality features cannot.

Explaining voice characteristics to novice voice practitioners-How successful is it? - Wiechmann, Jana; Rautenberg, Frederik; Wagner, Petra; Haeb-Umbach, Reinhold (20th International Congress of the Phonetic Sciences (ICPhS))

Reverberation as Supervision For Speech Separation - Aralikatti, Rohith; Boeddeker, Christoph; Wichern, Gordon; Subramanian, Aswin; Le Roux, Jonathan (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Mixture Encoder for Joint Speech Separation and Recognition - Berger, Simon; Vieting, Peter; Boeddeker, Christoph; Schlüter, Ralf; Haeb-Umbach, Reinhold (INTERSPEECH 2023)